(untitled) (World Bulletin of Management and Law, 2025)
The cause of unpredictable business in the emerging economies is due to the political insanity, financial volatility, technological shocks, customer expectations, and so on. The unprecedented challenges of the industry like banking, telecommunications and manufacturing test the resistance and the competitive ability of firms in Nigeria. This paper looked at the role of the strategic agility in the sense of the ability of firms to sense opportunities and threats, capture them, and reorganize resources, as being a critical channel through which the business policy can enhance competitive advantage in turbulent environments. The paper is guided by the Resource-Based View, Dynamic Capabilities Theory, and Contingency Theory in exploring the moderating role of business policy on the relationship between strategic agility and competitive advantage of Nigerian firms. Applying a conceptual framework and basing on the insights of the empirical literature, the study establishes that Nigerian companies that adopt the strategy of agility within their policies have a greater chance to defeat rivals in the turbulent markets. Methodologically, the paper adopts a survey design with hypothetical data from 250 firm analyzed using Pearson Moment Correlation Coefficient statistical tool (PPMCC). Strategic Agility (strategic sensitivity, resource fluidity and leadership unity) enhances competitive advantage of Nigerian firms, it was also established statistically that Business Policy significantly moderates the relationship between strategic agility and competitive advantage of Nigerian firms. The present paper also makes a contribution to the literature of business policy and strategy making through shedding light on how such agencies in emerging economies can manage through the volatility by adopting agile policies. Practical implications imply that managers ought to make agility a part of strategic policies, invest in digital transformation, and cultivate cultures of learning, to remain competitive.